Ecological and biological characteristics of saplings in relation to soil nutrients in secondary forest of Jenderak at Krau wildlife reserve, Pahang, Malaysia / Gufrin - Gufrin (2014)
A total of 8,951 saplings of the lowland dipterocarp secondary forest of Jenderak (2 ha plot) were recorded which comprised of 53 families, 136 genera, and 254 species. Result for diversity indices indicates that the secondary forest of Jenderak contains high diversity. Unfortunately, many plants are found to be in rare category; moreover, no dipterocarp sapling is found in the plots study. From Morisita Index of Dispersion, the five dominant saplings in the study area are found to be clumped. The soil compaction consists of two categories; moderate and severe. The carbon, nitrogen, phosphorus and C ratio were found low as compared to general study in primary forest; however, the exchangeable cations were considered high. Pearson’s correlation analyses showed that the soil physical properties significantly correlated to the soil nutrients (p < 0.05 and r value range from 0.296 to 0.775). Analysis of growth rate found that M. dispar was the fastest as compared to others. Multivariate analyses show that, the five highest IVi species have different ability to perform the canopy layer in the forest. The highest value of HC and CC was S. cauliflora whereas the lowest was Baccaurea sp.1. Correlation analysis found that soil physio-chemical properties have positive correlation with stem density (p < 0 .0 1 ); however, the correlation is weak based or r value below 0.5. The detrended correspondence analysis showed that the five commonest species are found to have different preferences in the soil characteristics. Based on the finding, the secondary forest of Jenderak requires appropriate planning for management in the future.